ARCHEOLOGICAL DRAWINGS WHEN GRAPHIC ENGINEERING DOCUMENTING OF EXCAVATIONS AT OBJECTS WITH CULTURAL AND HISTORICAL HERITAGE: ARCHEOLOGICAL DRAWINGS WHEN GRAPHIC ENGINEERING DOCUMENTING OF EXCAVATIONS AT OBJECTS WITH CULTURAL AND HISTORICAL HERITAGEThe suggested paper tries go present in brief and in general the types of archeological drawings when graphic engineering documenting of excavations at objects with cultural and historical heritage. - Stoyanov , Svetlozar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The suggested paper tries go present in brief and in general the types of archeological drawings when graphic engineering documenting of excavations at objects with cultural and historical heritage.